2022
DOI: 10.3389/fonc.2022.1087476
|View full text |Cite
|
Sign up to set email alerts
|

Cancer diagnosis in areas of conflict

Abstract: To date, many Arab countries within the Middle East are facing political, financial, and social instability from war and conflicts. These conflicts have led to severe resources shortages and sometimes complete breakdowns in cancer care and diagnosis. Cancer diagnosis at early stages is the most vital step in achieving optimal cancer care and outcomes. Shortages in cancer diagnostic services have meant that many people within areas of conflict are ultimately deprived of these services in their own countries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…8,37 It should be noted that this delay in diagnosis also complicates the management plans and poses higher financial burden on the patients and the system. 38 Our study also showed a 5-year survival rate of 0.1% and a 1-year survival rate of 13.1%; numbers that raise red flags when compared with survival rates worldwide. The most recent 5-year survival rate in the US 35,39 and in wealthier countries in the Middle East and North Africa region (commonly referred to as MENA) (eg, Qatar) 40 approximated 25%.…”
Section: Jama Network Open | Oncologysupporting
confidence: 64%
See 3 more Smart Citations
“…8,37 It should be noted that this delay in diagnosis also complicates the management plans and poses higher financial burden on the patients and the system. 38 Our study also showed a 5-year survival rate of 0.1% and a 1-year survival rate of 13.1%; numbers that raise red flags when compared with survival rates worldwide. The most recent 5-year survival rate in the US 35,39 and in wealthier countries in the Middle East and North Africa region (commonly referred to as MENA) (eg, Qatar) 40 approximated 25%.…”
Section: Jama Network Open | Oncologysupporting
confidence: 64%
“…Additionally, several reports described how the Syrian armed conflict affected the availability of specialized physicians, health care facilities, and screening programs, and increased the challenges in cancer diagnosis . It should be noted that this delay in diagnosis also complicates the management plans and poses higher financial burden on the patients and the system …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jordan has the largest population of refugees per capita in the world, with Syrians comprising the majority of the refugee population in Jordan [ 36 ]. Refugees face multiple challenges when it comes to cancer care in Jordan [ 37 ]. The Syrian refugee crisis has deeply affected the surrounding region since its onset in 2011, affecting more than five million Syrians that have sought refuge outside their homeland, predominantly in Turkey, Jordan, and Lebanon [ 38 ].…”
Section: Resultsmentioning
confidence: 99%